Semiotika Riffaterre dalam Puisi “Baju Baru” Karya Joko Pinurbo - Abdullah, Risen Dhawuh (Universitas Ahmad Dahlan, 2024)
It is undeniable that poets often convey ideas with signs in the form of words, clauses, even sentences, thereby creating implicit or implicit messages. Studying a poem requires structural and semiotic analysis, because poetry is a structure of meaningful signs. Joko Pinurbo's poems contain many messages from deep anxiety. This study seeks to explain the meaning of related poetry according to Riffaterre's Semiotics theory. This research is a qualitative descriptive study. The material object in this research is a poem by Joko Pinurbo